2014
DOI: 10.15252/msb.20145470
|View full text |Cite
|
Sign up to set email alerts
|

An organ boundary‐enriched gene regulatory network uncovers regulatory hierarchies underlying axillary meristem initiation

Abstract: Gene regulatory networks (GRNs) control development via cell type-specific gene expression and interactions between transcription factors (TFs) and regulatory promoter regions. Plant organ boundaries separate lateral organs from the apical meristem and harbor axillary meristems (AMs). AMs, as stem cell niches, make the shoot a ramifying system. Although AMs have important functions in plant development, our knowledge of organ boundary and AM formation remains rudimentary. Here, we generated a cellular-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 87 publications
2
124
0
Order By: Relevance
“…Genetic studies in Arabidopsis thaliana and other species have shown that AM initiation is regulated by several transcription factors, such as LATERAL SUPPRESSOR (LAS), REGULATOR OF AXILLARY MERISTEMS (RAX), and REVOLUTA (REV) (Talbert et al, 1995;Greb et al, 2003;Müller et al, 2006). Genetic and molecular studies revealed direct and indirect interactions among these genes in a regulatory network (Raman et al, 2008;Tian et al, 2014). WUS is expressed in the AM as in the SAM, but how WUS expression is established during AM initiation remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies in Arabidopsis thaliana and other species have shown that AM initiation is regulated by several transcription factors, such as LATERAL SUPPRESSOR (LAS), REGULATOR OF AXILLARY MERISTEMS (RAX), and REVOLUTA (REV) (Talbert et al, 1995;Greb et al, 2003;Müller et al, 2006). Genetic and molecular studies revealed direct and indirect interactions among these genes in a regulatory network (Raman et al, 2008;Tian et al, 2014). WUS is expressed in the AM as in the SAM, but how WUS expression is established during AM initiation remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…This process, known as floral evocation, results in new patterns of growth at the shoot apex, including production of flowers, and an increase in stem elongation, called bolting. Lateral organ boundaries are specialized domains of restricted growth that separate meristem and organ compartments and produce axillary meristems (for review, see Aida and Tasaka, 2006;Tian et al, 2014). Early in the transition to flowering, the IM produces cauline leaves and axillary meristems that develop as secondary inflorescences.…”
mentioning
confidence: 99%
“…52,46 Among those are ANT, CLF, AS1, AS2 that are expressed mainly in the growing organ and, CUC1, 2 and 3, the expression of which is restricted to the boundary domain. 43,46,52,54 The pattern of stress anisotropy is represented by color bar with green corresponding to the regions with lower stress anisotropy (central zone and organ) and orange in the boundary domain where stress anisotropy is maximal. This stress and gene expression pattern correlates with the distribution of the plant hormone auxin that has its local maximum where new organ initiates and its local minimum at the organ boundary.…”
mentioning
confidence: 99%